Spatio‐temporal dynamics of the common skate species complex: Evidence of increasing abundance. (12th October 2022) - McGeady, Ryan; Loca, Sophie L.; McGonigle, Chris
Abstract: Aim: The critically endangered common skate species complex is a large‐bodied and long‐lived batoid, which has experienced local extirpations and population declines over the past century mainly due to overfishing. Due to its decline, fisheries management measures were introduced to prevent further decline and fragmentation of populations. For example, in 2009, a landings prohibition was introduced in the European Union, which banned the retention of common skate onboard commercial fishing vessels with captured individuals to be discarded. We aimed to explore the spatial and temporal population dynamics of the common skate species complex, against the backdrop of changes in fisheries management measures. Location: Northeast Atlantic Ocean. Methods: We used publicly available fishery‐independent trawl survey data from several regions of the Northeast Atlantic shelf to examine trends in incidence and abundance for the common skate species complex. We also constructed a species distribution model to identify changes in the spatio‐temporal distribution of the common skate. Results: A sustained increase in the common skate species complex was evident in several areas of its distribution. An increase was observed in five separate trawl surveys encompassing distinct regions of its distribution. Despite the observed increase, little evidence of recolonizing previously extirpated areas was evident. Main Conclusions: The findings demonstrate the effectiveness of fisheries management measures in contributing to an increase in the common skate species complex. Such measures may also be effective if applied to numerous other batoid species currently threatened with extinction.